LOS SUSTRATOS DE LOS OBJETIVOS PEDAGÓGICOS EN LA ENSEÑANZA DE LA METODOLOGÍA DE LA INVESTIGACIÓN SOCIAL - Barriga, Omar; Henriquez, Guillermo (La Sociología en sus Escenarios, 2010)
Abstract. The traditional education of the methodology of the social research reflects an anachronistic vision of the education-learning: the professor gives knowledge and he gathers them to the student. Nevertheless, the new pedagogical philosophies take to us to reframe that exercise like one of construction of the knowledge on the part of the students with support of the professor. The free availability of information (mainly libraries and Internet) and the availability of specialized computer software makes the transmission less important of more important information and the handling of the same. Resumen. La enseñanza de la metodología de la investigación social refleja una visión anacrónica de la enseñanza-aprendizaje: el profesor entrega conocimientos y el alumno los recoge. Sin embargo, las nuevas filosofías pedagógicas nos llevan a replantear ese ejercicio como uno de construcción del conocimiento por parte de los alumnos con apoyo del profesor. La libre disponibilidad de información (principalmente bibliotecas e Internet) y la disponibilidad de programas informáticos especializados hace menos importante la transmisión de información y más importante el manejo de la misma.